2009
DOI: 10.1159/000193630
|View full text |Cite
|
Sign up to set email alerts
|

Additional Value of External Ultrasonography of the Neck after CT and PET Scanning in the Preoperative Assessment of Patients with Esophageal Cancer

Abstract: Introduction: Lymphatic dissemination of a (non-cervical) esophageal tumor to the neck is generally considered as distant metastasis. The aim of this study was to determine the additional value of external ultrasonography (US) to detect lymphatic metastasis to the neck after normal CT scan (CT) with or without normal PET scan (PET). Methods: Between January 2003 and December 2005, 306 patients were analyzed for esophageal cancer in our department. A total of 233 patients underwent both CT and external US of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
11
0
3
Order By: Relevance
“…Omloo et al . found an additional value of ultrasonography of the neck of 4% after normal CT and PET‐scanning; however, in that study, CT and PET were also performed subsequently instead of integrated PET‐CT scanning as in the present study 21 …”
Section: Discussionmentioning
confidence: 60%
“…Omloo et al . found an additional value of ultrasonography of the neck of 4% after normal CT and PET‐scanning; however, in that study, CT and PET were also performed subsequently instead of integrated PET‐CT scanning as in the present study 21 …”
Section: Discussionmentioning
confidence: 60%
“…Die B-Bild-Sonografie ist der Computertomografie im Nachweis von Halslymphknotenmetastasen gleichwertig oder geringfügig überlegen [282][283][284][285] und daher ergänzend sinnvoll, wenn nicht bereits im Rahmen der CT-Untersuchung eine Beurteilung der zervikalen Lymphknotenstationen erfolgt ist. Die ultraschallgestützte Feinnadelaspirationsbiopsie ist geeignet, den metastatischen Lymphknotenbefall histologisch zu sichern [283,[286][287][288].…”
Section: Hintergrundunclassified
“…This is suggested by two large series that found no additional value of external ultrasonography over PET/CT with regard to the detection of cervical lymph node metastases . Only one study has shown an additional value of 4% (3/74) of external ultrasonography over CT and PET imaging . However, in the latter study, the CT and PET scans were performed separately, which may yield lower diagnostic accuracy compared with integrated PET/CT scanning .…”
Section: Clinical Staging Of Esophageal Carcinomamentioning
confidence: 97%
“…31 However, in the latter study, the CT and PET scans were performed separately, which may yield lower diagnostic accuracy compared with integrated PET/CT scanning. 31 This implies that external ultrasonography may be omitted in the standard workup of patients with esophageal cancer. However, histopathologic confirmation in PET/CT-suspected lesions remains required because of potential false-positive lesions.…”
Section: Lymph Node Stagingmentioning
confidence: 97%
See 1 more Smart Citation